Kausatif-Pasif Morfologis Bahasa Indonesia dan Bahasa Jepang: Kajian Tipologi Bahasa - Kautsar, Haqi Sang; Subiyanto, Agus (KIRYOKU, 2025)
This study aims to describe the causative-passive morphological construction of Indonesian and Japanese and its unique features and constraints. This study offers a contribution in the form of an examination of a feature that is not found in all languages that have causative and passive markers. The data collection method used in this study is the observation method. Data on morphological causative-passive constructions were obtained from the LCC Indonesian 2023 corpus and the Balanced Corpus of Contemporary Japanese. The acceptability of causative-passive constructions in Indonesian was tested by the author as a native speaker of Indonesian and with 2 native speakers in Japanese. This study presents new findings, namely the expansion of Siewieska's (2013) passive criteria, the tendency of Indonesian and Japanese morphological causative-passive patterns along with the uniqueness and constraints of their construction. Based on the analysis results, the formation of morphological causative-passive in Indonesian is through the base form of intransitive verbs (36.99%), nouns (32.05%), adjectives (26.48%), adverbs (4,18%) with transitive verbs are unproductive. Meanwhile, in Japanese the formation is through the base form of nouns (77,76%), transitive verbs (17,97%), onomatopoeia (2,83%), and intransitive verbs (1,44%). Indonesian and Japanese have unique features that the morphological causative construction of transitive verbs can be passivized. The constraints on causative-passive morphological construction in Indonesian lie in emotional verbs. Meanwhile, in Japanese, constraints also occur in emotional verbs and in the suffix -gar-u which can be formed into causative but cannot be passivized.